Selection and Optimization of Asymmetric siRNA Targeting the Human c-MET Gene - Jo, Seul-gi (Korean Society for Molecular and Cellular Biology, 2011)
The silencing of specific oncogenes via RNA interference (RNAi) holds great promise for the future of cancer therapy. RNAi is commonly carried out using small interfering RNA (siRNA) composed of a 19 bp duplex region with a 2-nucleotide overhang at each 3’ end. This classical siRNA structure, however, can trigger non-specific effects, which has hampered the development of specific and safe RNAi therapeutics. Previously, we developed a novel siRNA structure, called asymmetric shorter-duplex siRNA (asiRNA), which did not cause the non-specific effects triggered by conventional siRNA, such as off-target gene silencing mediated by the sense strand. In this study, we first screened potent asiRNA molecules targeting the human c-MET gene, a promising anticancer target. Next, the activity of a selected asiRNA was further optimized by introducing a locked nucleic acid (LNA) to maximize the gene silencing potency. The optimized asiRNA targeted to c-MET may have potential as a specific and safe anticancer RNAi therapeutic.